P06.04.B Efficacy of Podoplanin-CAR-T Cells inex vivo Patient Derived Glioblastoma Organoids. (5th September 2022) - Diener, L; Goedert, N; Schulz, T; Monoranu, C; Ernestus, R; Hagemann, C; Löhr, M; Nerreter, T; Dufner, V
Abstract: Background: Glioblastoma (GBM) is the most prevalent malignant brain tumor in adults. Recent immunotherapeutic approaches led to promising effects both in vitro and in preclinical animal models. However, tumor heterogeneity, antigen escape mechanisms and complex interactions with the tumor microenvironment (TME) hinder their clinical breakthrough. Thus, patient derived ex vivo models are needed to test new therapeutical approaches. Genetically modified T cells expressing a chimeric antigen receptor (CAR) hold enhanced affinity for tumor associated antigens. As Podoplanin (PDPN) shows stable and increased expression in GBM, it is a suitable target antigen. When activated, CAR-T cells initiate the triad of cytokine release, T cell proliferation and target cell apoptosis. We evaluated the performance of PDPN-CAR-T cells in GBM patient derived organoids (PDO). Material and Methods: PDOs were generated from freshly resected GBM tissue and could be cultured successfully up to several months. We assessed PDPN expression of PDOs via immunohistochemistry (IHC) prior to treatment. PDPN-CAR T cells were generated from peripheral blood mononuclear cells of healthy donors via lentiviral transduction and expansion. The transduction rate was assessed by flow cytometry prior to application. PDOs treated with untransduced T cells served as controls. PDOs were incubated with a preset number of PDPN-CAR T cells at a E:T ratio of 1:4 and were examined microscopically to register morphological disintegration after 48h. Immunofluorescence staining was conducted to detect proliferating CD4 + CART cells (CD4 + / Ki67 + ) after 72h and cytokine release of IFN-γ was determined via ELISA after 20h. Results: In total, PDOs from three patients were treated with PDPN-CART cells. All of them expressed the antigen according to IHC staining. All incubated PDOs presented clear disintegration of the circular organoid shape up to total dissolving, whereas control PDOs stayed intact. CD4 + CART cells showed extensive proliferation at a mean rate of 79.8% ± 6, 59% which was significant for two PDOs in comparison to control PDOs (p = 0.48, p < 0.01). PDPNCART cells exhibited significantly elevated IFN-γ release in all PDOs (p < 0.01). Conclusion: We here describe PDPN as a promising target and proved effectiveness of PDPN-CAR-T cells in an ex vivo 3D model. Additional ex vivo models like tumor slice cultures might be crucial to evaluate effectiveness of CAR-T cell therapy. PDPN-CAR-T cells should be tested in these ex vivo as well as in vivo GBM models alone and in a combined approach with CARs targeting additional antigens in order to overcome tumor heterogeneity.